2004
DOI: 10.21236/ada465595
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Breathing Rates: Defining Anticipated Values and Ranges for Respirator Certification Testing

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defense, Washington Headquarters Services, Directorate for Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…19 A recent review concluded that respirator use has little impact on minute volume during resting or low-intensity work conditions like those normally encountered in health care environments. 20 Mean absolute increases in transcutaneous carbon dioxide with the EAPR at 1.7 mph (13.2 mm Hg) and 2.5 mph (12.1 mm Hg) were not significantly different from controls (P 5 .09, P 5 .27, respectively). Of concern is the finding that mean transcutaneous carbon dioxide levels, averaged over the course of the last 15 minutes of the EAPR use, were elevated (ie, .45 mm Hg) in 4 of 10 subjects at the 1.7-mph work rate (range, 46-56 mm Hg) and 5 of 10 subjects at the 2.5-mph work rate (range, 45.4-62.8 mm Hg), despite the EAPR being equipped with an exhalation valve that presumably allows for a smaller proportion of the exhaled breath (and associated carbon dioxide) to be retained in the respirator dead space (all subjects were asymptomatic of hypercapnia).…”
Section: Discussionmentioning
confidence: 78%
“…19 A recent review concluded that respirator use has little impact on minute volume during resting or low-intensity work conditions like those normally encountered in health care environments. 20 Mean absolute increases in transcutaneous carbon dioxide with the EAPR at 1.7 mph (13.2 mm Hg) and 2.5 mph (12.1 mm Hg) were not significantly different from controls (P 5 .09, P 5 .27, respectively). Of concern is the finding that mean transcutaneous carbon dioxide levels, averaged over the course of the last 15 minutes of the EAPR use, were elevated (ie, .45 mm Hg) in 4 of 10 subjects at the 1.7-mph work rate (range, 46-56 mm Hg) and 5 of 10 subjects at the 2.5-mph work rate (range, 45.4-62.8 mm Hg), despite the EAPR being equipped with an exhalation valve that presumably allows for a smaller proportion of the exhaled breath (and associated carbon dioxide) to be retained in the respirator dead space (all subjects were asymptomatic of hypercapnia).…”
Section: Discussionmentioning
confidence: 78%
“…Consensus is not found in the literature for a representative occupational ventilation rate for PIF. However, the range of PIFs for the 95 th percentile minute volume for occupational tasks is estimated to range between 182 and 295 L/min (Caretti et al, 2004). Therefore, the choice of 150 L/min may underestimate a "worst case" PIF.…”
Section: Respirator Selection and Test Conditionsmentioning
confidence: 99%
“…First, the rate established by the NIOSH protocol (85 L/min) may be exceeded during more strenuous occupational tasks. Second, modern FFR media relies upon electret properties for much of the overall filtration efficiency (Martin and Moyer, 2000;Caretti et al, 2004). For ultrafine particles, the primary filter capture mechanisms are diffusion and electrostatic interaction, which are both strongly dependent upon respirator face velocity.…”
Section: Respirator Selection and Test Conditionsmentioning
confidence: 99%
“…(12) Additionally, peak flow rates measured during exhaustive work can exceed the 85 L/min NIOSH certification flow. (14) A high breathing rate and particles sized within the MPPS range may result in aerosol penetration exceeding that associated with the stated certification level.…”
Section: Introductionmentioning
confidence: 99%